Upadacitinib and Cardiovascular Adverse Events in Rheumatoid Arthritis: A Systematic Review and Meta-Analysis. - Omidi, Fatemeh; Delkash, Parisa; Nasiri, Mohammad Javad; Mirsaeidi, Mehdi (Current Rheumatology Reviews, 2025)
BackgroundUpadacitinib, a Janus kinase (JAK) inhibitor used in rheumatoid arthritis treatment, has prompted safety concerns due to potential cardiovascular adverse events. However, current evidence does not provide a definitive conclusion.MethodsWe conducted a comprehensive systematic review of the literature up until March 15, 2024, utilizing databases like PubMed/Medline, Embase, and Cochrane CENTRAL. A meta-analysis approach was used to derive pooled odds ratios (OR) along with their 95% confidence intervals (CI) to assess the cardiovascular risk associated with upadacitinib. Publication bias was evaluated using Begg's and Egger's tests.ResultsOur meta-analysis included six studies with a total of 4,202 participants. For the 15 mg dosage of Upadacitinib, the pooled OR was 1.20 (95% CI: 0.3-4.3), indicating a nominal, non-significant increase in the risk of cardiovascular adverse events. Analysis of the 30 mg dosage presented a pooled OR of 2.37 (95% CI: 0.6-9.1), pointing to a higher, yet statistically insignificant, potential risk. The absence of publication bias was confirmed through Begg's and Egger’s tests.ConclusionThe analysis suggests a potential heightened cardiovascular risk associated with Upadacitinib, more so with the 30 mg dosage. Nevertheless, the lack of statistical significance and the wide confidence intervals necessitate a prudent approach to these findings. Tailored treatment strategies, rigorous monitoring, and further empirical studies are crucial for refining the safety profile of upadacitinib and ensuring optimal patient outcomes.
Keywords: cardiovascular adverse events